Resting and post-exercise serum biomarkers of cardiac and skeletal muscle damage in adolescent runners - Nie, J.; Tong, T. K.; George, K.; Fu, F. H.; Lin, H.; Shi, Q. (Scandinavian Journal of Medicine & Science in Sports, 2011)
This study examined the response of serum biomarkers of cardiac and skeletal muscle damage at rest and after a routine workout of 21 km run in 12 male adolescent (16.2±0.6 years) long-distance runners. Biomarkers of cardiac [troponins (cTnT, cTnI), creatine kinase MB mass (CK-Mbmass)] and skeletal muscle [creatine kinase (CK), lactate dehydrogenase (LDH), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and hydroxybutyrate dehydrogenase (HBD)] damage were assayed at rest, 2, 4 and 24 h post-exercise. At rest, cTnT and cTnI were not detectable; however, CK, CK-MBmass, AST, ALT and HBD were above corresponding clinical cut-off values. Post-exercise significant elevations above rest were observed for all biomarkers, except ALT, 2 and 4 h following the run, and remained elevated in cTnI, CK, CK-MBmass, LDH and AST 24 h post-workout. A significant increase in data points above clinical cut-off values from rest to post-exercise was reported for cTnT, cTnI and CK at 2 and 4 h, and in cTnI and CK 24 h post-exercise. In conclusion, a 21 km run in adolescent runners increased post-exercise biomarkers of cardiac and skeletal muscle damage.